Pirfenidone ameliorates alcohol-induced promotion of breast cancer in mice - Li, Hui; Xu, Mei; Chen, Danlei; Wen, Wen; Luo, Jia (Frontiers in Oncology, 2024)
Alcohol consumption increases the risk of breast cancer and promotes cancer progression. Alcohol exposure could affect both processes of the mammary carcinogenesis, namely, the cell transformation and onset of tumorigenesis as well as cancer aggressiveness including metastasis and drug resistance/recurrence. However, the cellular and molecular mechanisms underlying alcohol tumor promotion remain unclear. There are four members of the mammalian p38 mitogen-activated protein kinase (MAPK) family, namely, p38α, p38β, p38 and p38δ. We have previously demonstrated alcohol exposure selectively activated p38 MAPK in breast cancer cells in vitro and in vivo. Pirfenidone (PFD), an antifibrotic compound approved for the treatment of idiopathic pulmonary fibrosis, is also a pharmacological inhibitor of p38 MAPK.This study aimed to determine whether PFD is useful to inhibit alcohol-induced promotion of breast cancer.Methods: Female adolescent (5 weeks) MMTV-Wnt1 mice were exposed to alcohol with a liquid diet containing 6.7% ethanol. Some mice received intraperitoneal (IP) injection of PFD (100 mg/kg) every other day. After that, the effects of alcohol and PFD on mammary tumorigenesis and metastasis were examined.Results: Alcohol promoted the progression of mammary tumors in adolescent MMTV-Wnt1 mice.Treatment of PFD blocked tumor growth and alcohol-promoted metastasis. It also significantly inhibited alcohol-induced tumorsphere formation and cancer stem cell (CSC) population.PFD inhibited mammary tumor growth and alcohol-promoted metastasis. Since PFD is an FDA-approved drug, the current findings may be helpful to re-purpose its application in treating aggressive breast cancer and alcohol-promoted mammary tumor progression.